ALS gene overexpression and enhanced metabolism conferring Digitaria sanguinalis resistance to nicosulfuron in China - Wang, Ruolin; Sun, Ying; Lan, Yuning; Wei, Shouhui; Huang, Hongjuan; Li, Xiangju; Huang, Zhaofeng (Frontiers in Plant Science, 2023)
Crabgrass (Digitaria sanguinalis) is a common malignant weed in corn fields in China. Recently, the acetolactate synthase (ALS) inhibitor, nicosulfuron, has shown decreasing efficacy against crabgrass. In order to define the molecular basis of crabgrass resistance to nicosulfuron, we characterized the resistance of crabgrass populations collected from Beijing, Heilongjiang, Jilin and Anhui provinces. Whole-plant dose-response results indicated that only population collected in Heilongjiang province (HLJ) had developed low level of resistance to nicosulfuron compared with the sensitive population (SD22). No known resistant mutation of ALS gene was found in HLJ population. The real-time fluorescence quantitative PCR results showed that the ALS gene copy number did not differ significantly between the HLJ and SD22 populations. However, the ALS gene expression in the HLJ was 2.07-fold higher than that of the SD22 population at 24 h after treatment with nicosulfuron. Pretreatment with the cytochrome P450 (CYP450) inhibitor malathion, piperonyl butoxide (PBO), and the glutathione S-transferase (GST) inhibitor 4-Chloro-7-nitro-1,2,3-benzoxadiazole (NBD-Cl) all partially reversed HLJ resistance. Among them, the synergistic effect of PBO and nicosulfuron is the most significant. This is the first report of resistance to nicosulfuron in crabgrass through ALS gene overexpression and possible metabolic resistance.